(untitled) (Scientific journal of the Fergana State University, 2023)
The article gives an idea of the techniques for achieving the productivity of foreign learning activities. According to the author, a foreign learner should consciously master the phonetics, morphology and linguistics of the studied foreign language and be able to use them in communication.